2020
DOI: 10.3390/diagnostics10110934
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Diagnosis of Malignancies Based on the Analysis of Markers in Exhaled Air

Abstract: Novel non-invasive methods for the diagnosis of malignancies should be effective for early diagnosis, reproducible, inexpensive, and independent from the human factor. Our aim was to establish the applicability of the non-invasive method, based on the analysis of air exhaled by patients who are at different stages of oropharyngeal, larynx and lung cancer. The diagnostic device includes semiconductor sensors capable of measuring the concentrations of gas components in exhaled air, with the high sensitivity of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The last decade has seen an uprising trend in disease diagnosis through exhaled air analysis. This spans from malignancy detection, 15 , 16 through analysis of metabolic states, 17 , 18 to host and invader diagnostics. 19 , 20 , 21 The term “breath-print” has been coined to express the multiplicity of techniques that have been applied to analyze the various contents of exhaled air, including particulate matter, aerosol, and gaseous content.…”
Section: Introductionmentioning
confidence: 99%
“…The last decade has seen an uprising trend in disease diagnosis through exhaled air analysis. This spans from malignancy detection, 15 , 16 through analysis of metabolic states, 17 , 18 to host and invader diagnostics. 19 , 20 , 21 The term “breath-print” has been coined to express the multiplicity of techniques that have been applied to analyze the various contents of exhaled air, including particulate matter, aerosol, and gaseous content.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers first discovered that ordinary domestic dogs with basic training could precisely distinguish between breath samples from lung and breast cancer patients and normal subjects’ breath samples ( 73 ). Later, many studies investigated the value of VOCs in human cancer ( 74 , 75 ). To date, studies have revealed that VOCs, as metabolites of the body, can directly reflect the metabolism of body tissues and cells.…”
Section: Application Of Ms In the Diagnosis And Prognosis Of Pcmentioning
confidence: 99%